Strategies for timing of nest departure in the common guillemot Uria aalge - Johansen, Malin Kjellstadli (UiT Norges arktiske universitet, 2017)
Duration of parental care in avian species varies widely, from altricial to precocial species. The seabird family Alcidae is unique among birds in the variation of mass and age at nest departure. The common guillemot Uria aalge exhibits an intermediate nest departure, where chicks leave the nest flightless and only at a quarter of adult body size. The aim of this study was to examine factors controlling the age, weight and wing-length of the juveniles at nest departure. To assess this I followed common guillemot families including both parents and chick, from hatching to post-departure. The results showed that females in better body condition had older chicks at departure, than females in lower body condition. Both paternal and maternal stress-levels and their body condition had a significant influence on the weight and wing-length of the chicks at departure. Indications of strong synchronized departure events during the evening hours were found, where 30 juveniles, followed in the present study, departed the colony during five evenings. The synchronized departure events were highly weather dependent – strong winds were not favoured. I did not find strong support for that parental body condition or short-term changes in food availability during the chick-rearing period had any impact on the juveniles’ age at departure. The findings indicate that only the maternal body condition affects the juvenile age at departure. Whether the maternal condition alone controls the timing of nest departure, or if it is controlled by high energy gain at sea and increased food availability, remains unknown.